Akun Instagram @kampusmerdeka.ri Dan Minat Mahasiswa Mengikuti Merdeka Belajar Kampus Merdeka - Arifah, Intan Zahra; Abidin, Zainal; Oxcygentri, Oky (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study entitled " Instagram account @kampusmerdeka.ri and students' interest in participating in Merdeka Learning at Merdeka Campus" aims to identify and measure the contents of messages uploaded to Instagram @kampusmerdeka.ri account content on students' interest in participating in the MBKM program. This study uses the uses and effect theory. This research is a quantitative research with an explanatory approach. The population of this study is followers of the Instagram account @kampusmerdeka.ri. The data collection method used is a questionnaire. The results of the study are based on hypothesis t testing, simple linear regression analysis, coefficient of determination, normality test gives the result that variable X (the contents of messages uploaded to Instagram @kampusmerdeka.ri) has a significant positive effect on variable Y (student interest in joining the MBKM program).